Strategic Leadership Styles in The Digital Era: Lessons From Russia, The United States, and Israel for Indonesia's Cyber Defense Doctrine - Agung Widodo; Arif Harianto; Andy Mustafa Akad; Joko Prasetyo (Journal of Social Research, 2025)
The development of information technology has presented new challenges in the defense sector, especially in the cyber domain. Threats such as ransomware attacks, data leaks, and the potential for cyber warfare are not only technical, but also strategic because they can disrupt national stability and state sovereignty. This background prompted the study to examine strategic leadership in cyber defense by comparing the experiences of three countries: Russia, the United States, and Israel. This research aims to identify the strategic leadership patterns of cyber defense in the three countries, analyze their similarities and differences, and formulate relevance for Indonesia. The method used is a qualitative approach with case studies and literature studies to gain a comprehensive understanding. The results of the analysis show that Russia emphasizes the centralization of command and offensive forces, the United States prioritizes multi-sectoral collaboration, while Israel stands out in innovation and civil-military synergy. The similarity of the three is that placing cyber strategic leadership as a national issue, not just a technical one. Its relevance for Indonesia is the need to build an integrated national cyber defense doctrine, based on national values, and involving all components of the nation. In conclusion, visionary, collaborative, and innovative strategic leadership will strengthen Indonesia's cyber defense, protect digital sovereignty, and support the realization of Golden Indonesia 2045.